Old Swedish morphology - Språkbanken Text (University of Gothenburg, 2024)
Old Swedish morphology from Söderwall and Schlyter

Fornsvensk morfologi ur Söderwall och Schlyter
Fornsvensk morfologi
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik